When work–family guilt becomes a women's issue: Internalized gender stereotypes predict high guilt in working mothers but low guilt in working fathers - Aarntzen, Lianne; Derks, Belle; van Steenbergen, Elianne; van der Lippe, Tanja (British Journal of Social Psychology, 2023)
Les stéréotypes de genre prescrivent aux mères, mais pas aux pères, de donner la priorité à leur famille plutôt qu’à leur travail. Par conséquent, l’intériorisation des stéréotypes de genre peut prédire une culpabilité plus élevée chez les mères que chez les pères dans des situations où ils privilégient leur travail plutôt que leur famille. L’étude 1 (135 mères et 116 pères) a en effet révélé que plus les stéréotypes de genre implicites des pères étaient forts (mesurés à l’aide d’une tâche d’association implicite genre-carrière), moins les pères se déclaraient coupables dans une situation fictive d’interférence du travail dans la famille. Bien que les mères aient en moyenne déclaré une culpabilité plus élevée que les pères, cet effet n’a pas été atténué par leurs stéréotypes de genre implicites. L’étude 2 (étude du journal quotidien auprès de 105 mères) a toutefois révélé des preuves de l’effet modérateur des stéréotypes de genre implicites sur la culpabilité des mères qui travaillent. Plus les stéréotypes de genre implicites des mères étaient forts, plus elles déclaraient avoir des conflits entre le travail et la famille et de la culpabilité les jours où elles travaillaient de longues heures. Ces résultats montrent que les stéréotypes de genre implicites façonnent la façon dont les parents perçoivent leurs choix travail-famille.
Keywords: 2000 à aujourd'hui; 2020-2029; care; charge mentale; conciliation famille-travail; culpabilité; discipline; europe; famille; maternité; pays-bas; projet charge mentale; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; émotions

Être lesbienne, gay ou bisexuel·le dans une organisation française : le rôle des micro-agressions homonégatives et l’effet médiateur du climat de diversité sexuelle dans le choix de dévoiler ou dissimuler son orientation sexuelle - Grelier, Anaelle; Demarque, Christophe; Suchier, Johann; Dupoirier, Samuel (Pratiques psychologiques, 2021)
Les personnes lesbiennes, gaies et bisexuelles (LGB) peuvent mobiliser différentes stratégies pour dévoiler ou cacher leur orientation sexuelle sur leur lieu de travail. Cette étude a pour objectif d'explorer les relations entre les micro-agressions homonégatives (MAH) perçues au travail et ces stratégies, ainsi que l'effet médiateur du climat organisationnel de diversité sexuelle dans ces relations. Un échantillon de 135 salariés·e·s LGB a répondu à un questionnaire en ligne portant sur ces trois variables. Les données ont été traitées par le biais de régressions linéaires simples et de méthodes d'analyse en pistes causales. Les résultats ont mis en avant que l'effet des MAH sur la gestion de son identité sexuelle au travail était médiatisé par le climat de diversité sexuelle. Il existe également une relation directe positive entre les MAH et le dévoilement. Les résultats sont discutés à la lumière de la littérature existante sur le sujet. Des perspectives aux niveaux systémiques et individuels pour soutenir le climat de diversité sexuelle et réduire la discrimination vécue par les salarié·e·s LGB sont envisagées.
Number: 1
Keywords: discipline; europe; france; identités LGBTQIA2+; psychologie; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail; violences

The new lesbian aesthetic? Exploring gender style among femme, butch and androgynous sexual minority women - Gunn, Audrey; Hoskin, Rhea Ashley; Blair, Karen L. (Women's Studies International Forum, 2021)
The current study explored sexual minority women’s gender aesthetic and style by using van Anders’ (2015) sexual configurations theory (SCT), which allows for nuance in the measurement of gender/sex research. Previous research on sexual minority women has suggested a markedly masculine “Lesbian Aesthetic” (Huxley et al., 2014) and has connected aesthetic expression to internalized homophobia and levels of outness such that sexual minority women categorized as more feminine report higher rates of internalized homophobia and identity concealment. However, the bulk of past research used dichotomous measures of assessing gender and predated an ostensible shift in LGBTQ+ identities. To update this body of research, the current study explored gender aesthetics by asking sexual minority women to map their gender expression using SCT diagrams and complete measures of outness and internalized homophobia. We found no significant group differences in internalized homophobia or outness for femme, butch, and androgynous participants. Content analyses of gender diagrams suggest that the gender aesthetics of sexual minority women are neither monolithic nor masculine but may be beginning to lean towards the feminine and most certainly encompass a complex and diverse range of expressions
Keywords: amériques; approches et analyses; canada; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; lesbophobie; psychologie; queer; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Beyond the superordinate categories of “Gay Men” and “Lesbian Women”: Identification of gay and lesbian subgroups - McCutcheon, Jessica M.; Morrison, Melanie A. (Journal of Homosexuality, 2021)
Nation-wide opinion polls and social scientific studies indicate that evaluations of gay men and lesbian women have become increasingly favourable. These positive trends do not explain the widespread discrimination experiences being reported. To assist researchers in investigating attitudes towards gay and lesbian persons, the current research examines whether there are multiple “types” that are identifiable and salient. Two Canadian studies (Ns = 67 and 206) were conducted to establish the presence of gay and lesbian subgroups. Using subgroups generated by Study 1 participants, community and student sub-samples selected those they perceive to exist. Results indicated that, for gay men, the subgroups Drag Queen and Flamboyant emerged, as did Butch for lesbian women. Amongst students, Closeted and Feminine also emerged for gay men, as well as Feminist and Tomboy for lesbian women. These findings have implications for contemporary research on gay- and lesbian-related attitudes and the methodology used to assess them.
Keywords: amériques; canada; discipline; identités LGBTQIA2+; psychologie; ressource en ligne; régions géographiques; sciences humaines

Psychologie du sexisme : des stéréotypes de genre au harcèlement sexuel - Faniko, Klea; Dardenne, Benoit (De Boeck Supérieur, 2021)
"Depuis plusieurs années et sous l'impulsion de mouvements sociaux comme #MeToo, de nombreuses affaires de violences sexistes et sexuelles, impliquant des personnalités publiques ou des institutions connues, éclatent au grand jour dans les médias. Ces différents témoignages de femmes mettent en lumière l'ampleur des violences sexistes et sexuelles dans le monde. Comment expliquer une telle prévalence? Quels processus psychologiques peuvent conduire à l'apparition de stéréotypes, de préjugés et de discriminations sexistes? L'objectif de cet ouvrage, rassemblant 45 chercheurs francophones, est de contribuer à la compréhension des conséquences des discriminations sexistes, mais surtout d'aider à décrypter leurs mécanismes. Le phénomène s'avère complexe et très souvent subtil, prenant diverses formes et étant profondément inscrit dans les rouages de la société et des rapports humains. En plus des analyses présentées dans l'ouvrage, différentes pistes d'action sont proposées pour les entreprises et les institutions souhaitant promouvoir un environnement de travail inclusif."–Quatrième de couverture.
Section: xxi, 326 pages : illustrations ; 24 cm.
Keywords: EDI; approches et analyses; cours; discipline; discours dominant; discriminations; harcèlement sexuel; outils; outils didactiques; premier cycle; psy4910; psychologie; sciences humaines; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; violences

Microaggressions and philosophy - Freeman, Lauren; Weekes Schroer, Jeanine (Routledge, 2020)
"This is one of the first books to offer a comprehensive philosophical treatment of microaggressions. Its aims are to provide an intersectional analysis of microaggressions that cuts across multiple groups and dimensions of oppression and marginalization, and to engage a variety of perspectives that have been sidelined within the discipline of philosophy. The volume gathers a diverse group of contributors: philosophers of color, philosophers with disabilities, philosophers of various nationalities and ethnicities, and philosophers of several genders and gender identities. Their unique frames of analysis articulate both how the concept of microaggressions can be used to clarify and sharpen our understanding of subtler aspects of oppression and how analysis, expansion, and reconceiving the notion of a microaggression can deepen and extend its explanatory power. The essays in the volume are divided into four thematic parts. The essays in Part I seek to defend microaggressions from common critiques and to explain their impact beyond the context of college students. In Part II the contributors set forth a framework for legitimizing microaggressions research that takes into account issues of measurement, scale, and replication. Part III explores the harms of microaggressions. The chapters show how small slights can accumulate to produce significant harm at the macro level, demonstrate how microaggressions contribute to epistemic harm, and establish novel understandings of racial and accent-triggered microaggressions. Finally, Part IV addresses issues of disability and ableism within the context of microaggressions. It includes commentary on transgender athletes, disciplinary techniques for bodily nonconformity, ableist exceptionalism, and deafness. Microaggressions and Philosophy features cutting-edge research on an important topic that will appeal to a wide range of students and scholars across disciplines. It includes perspectives from philosophy of psychology, empirically informed philosophy, feminist philosophy, critical race theory, disability theory, philosophy of language, philosophy of science, and social and political philosophy"– Provided by publisher.
Keywords: EDI; approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; histoire et politique; hétérosexisme; intersectionnalité; inégalités; micro-agression; philosophie; psychologie; racisme; sciences humaines; sexisme; sofia; systèmes d'oppressions; thématiques; transphobie; violences; études critiques de la race; études critiques du handicap

Sex & gender: An introduction - Lips, Hilary M. (Waveland Press, Inc., 2020)
Are sex and gender really two different things? How malleable is gender identity? Do both gender and sex have to be conceptualized as binaries—as having two distinct but complementary categories? Should we emphasize gender differences, or is that the wrong question? When should we call a gender difference “small”? Are women really “nonaggressive” or does that label stem from stereotyping? How does subtle or “modern” sexism work on its targets? Scholarship on these and other gender-related questions has exploded in recent years. Hilary Lips synthesizes that research for students in an accessible and readable way. Concepts on sex and gender are presented with the social context in which they were developed. As in previous editions, Lips takes a multicultural approach, discussing the gender experiences of people from a wide range of races, cultures, socioeconomic statuses, and gender and sexual identities. She emphasizes empirical research but takes a critical approach to that research.
Keywords: analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; construction du savoir; corps; cours; discipline; discours dominant; essentialisation; hétérosexisme; identité; identité sexuelle; inégalités; premier cycle; psy4910; psychologie; santé; sciences humaines; sexe/genre; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; trs3550; études de genres

Companion to sexuality studies - Naples, Nancy A. (Wiley Blackwell, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités

The future of sex and gender in psychology: Five challenges to the gender binary - Hyde, Janet Shibley; Bigler, Rebecca S.; Joel, Daphna; Tate, Charlotte Chucky; van Anders, Sari M. (American Psychologist, 2019)
The view that humans comprise only two types of beings, women and men, a framework that is sometimes referred to as the “gender binary,” played a profound role in shaping the history of psychological science. In recent years, serious challenges to the gender binary have arisen from both academic research and social activism. This review describes 5 sets of empirical findings, spanning multiple disciplines, that fundamentally undermine the gender binary. These sources of evidence include neuroscience findings that refute sexual dimorphism of the human brain; behavioral neuroendocrinology findings that challenge the notion of genetically fixed, nonoverlapping, sexually dimorphic hormonal systems; psychological findings that highlight the similarities between men and women; psychological research on transgender and nonbinary individuals’ identities and experiences; and developmental research suggesting that the tendency to view gender/sex as a meaningful, binary category is culturally determined and malleable. Costs associated with reliance on the gender binary and recommendations for future research, as well as clinical practice, are outlined. (PsycINFO Database Record (c) 2019 APA, all rights reserved).
Keywords: LGBTQIA2+; activisme; analyse critique; approches et analyses; cours; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; queer; revue de la littérature; sciences humaines; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; études de genres

Mothers and mental labor: A phenomenological focus group study of family-related thinking work - Robertson, Lindsey G.; Anderson, Tamara L.; Hall, M. Elizabeth Lewis; Kim, Christina Lee (Psychology of Women Quarterly, 2019)
Le travail mental est une composante peu étudiée et longtemps invisible du travail familial. Les chercheurs ont décrit le travail mental comme important, éprouvant et effectué de manière disproportionnée par les mères par rapport aux pères. Cependant, les définitions opérationnelles utilisées dans ces études n'étaient que préliminaires et manquaient de terminologie unifiée. En réponse aux appels à une vision élargie du travail domestique et à de meilleures définitions de son contenu, nous avons entrepris une enquête phénoménologique sur le travail mental familial effectué par les mères. Notre analyse phénoménologique interprétative de sept entretiens de groupe a produit une définition du travail mental des mères et de ses composantes qui était empiriquement fondée sur l'expérience vécue des mères de jeunes enfants ( N = 25). Distinct des tâches ménagères, de la garde des enfants et du travail émotionnel, le travail mental est apparu comme une activité de réflexion effectuée dans le but d'atteindre des objectifs familiaux. Nous avons identifié six formes de travail mental : (a) la planification et l'élaboration de stratégies, (b) le suivi et l'anticipation des besoins, (c) la métaparentalité, (d) la connaissance (apprentissage et mémorisation), (e) la pensée managériale (y compris la délégation et l'instruction) et (f) l'autorégulation. Toutes les mères participantes se sont présentées comme le principal travailleur mental de leur famille, quel que soit leur statut d'emploi ou le niveau d'implication de leur partenaire. Notre description du travail mental peut aider les parents, les chercheurs, les cliniciens, les décideurs politiques et les éducateurs à reconnaître, à valoriser et à mieux tenir compte de la dynamique du travail mental à l'œuvre dans la construction de la vie familiale, la reproduction des rôles de genre et la perpétuation des écarts entre les sexes dans la division du travail familial et la charge mentale.
Keywords: 2000 à aujourd'hui; amériques; charge mentale; discipline; famille; famille hétérosexuelle; maternité; projet charge mentale; psychologie; périodes historiques; régions géographiques; sciences humaines; thématiques; travail; travail familial; travail invisible; états-unis

Dancing backwards in high heels: Female professors experience more work demands and special favor requests, particularly from academically entitled students - El-Alayli, Amani; Hansen-Brown, Ashley A.; Ceynar, Michelle (Sex Roles, 2018)
Although the number of U.S. female professors has risen steadily in recent years, female professors are still subject to different student expectations and treatment. Students continue to perceive and expect female professors to be more nurturing than male professors are. We examined whether students may consequently request more special favors from female professors. In a survey of professors (n = 88) across the United States, Study 1 found that female (versus male) professors reported getting more requests for standard work demands, special favors, and friendship behaviors, with the latter two mediating the professor gender effect on professors’ self-reported emotional labor. Study 2 utilized an experimental design using a fictitious female or male professor, with college student participants (n = 121) responding to a scenario in which a special favor request might be made of the professor. The results indicated that academically entitled students (i.e., those who feel deserving of success in college regardless of effort/performance) had stronger expectations that a female (versus male) professor would grant their special favor requests. Those expectations consequently increased students’ likelihood of making the requests and of exhibiting negative emotional and behavioral reactions to having those requests denied. This work highlights the extra burdens felt by female professors. We discuss possible moderators of these effects as well as the importance of developing strategies for preventing them. © 2017, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: amériques; approches et analyses; discipline; femmes professeures; milieux universitaires; projet charge mentale; psychologie; psychologie sociale; rapports sociaux de sexe; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; travail émotionnel; états-unis

Linking job work hours to women’s physical health: The role of perceived unfairness and household work hours - Thomas, Candice L.; Laguda, Emem; Olufemi-Ayoola, Folasade; Netzley, Stephen; Yu, Jia; Spitzmueller, Christiane (Sex Roles, 2018)
Although the relationship between job work hours and women’s physical health has been examined, limited empirical research examines the family demand conditions that explain this relationship. Given the challenge of integrating work and family demands, we examine the boundary conditions under which job hours relate to women’s physical health by integrating the influences of household work hours, perceived unfairness of division of household labor, and traditional gender ideology. Using a large, multi-national archival dataset, our results show that women working long job hours are more likely to report decreased physical health and that this relationship is moderated by the hours and fairness perceptions of household labor: The lowest physical health was observed at high job hours and high household hours and also when women felt that they did less than their fair share of household labor. However, looking at the slopes of these relationships, the negative relationship between job hours and physical health was stronger when women worked lower household hours or felt that they contributed less than their fair share of household labor—suggesting that maintaining a contribution to household labor might be important for working women. Furthermore, these results suggest that policy and organizational interventions aimed at supporting women’s physical health could take their household labor contributions and fairness perceptions into account when assessing the negative impact of high job work hours. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; conciliation famille-travail; culpabilité; discipline; division sexuelle du travail; famille; projet charge mentale; psychologie; psychologie sociale; périodes historiques; rapports sociaux de sexe; sciences humaines; thématiques; travail; travail domestique

Gender: Psychological perspectives - Brannon, Linda (Routledge, 2017)
"Gender: Psychological Perspectives" synthesizes the latest research on gender to help students think critically about the differences between research findings and stereotypes, provoking them to examine and revise their own preconceptions. The text examines the behavioral, biological, and social contexts in which women and men express gendered behaviors. The text's unique pedagogical program helps students understand the portrayal of gender in the media and the application of gender research in the real world. – From publisher's description. Contenu : Preface – Acknowledgements – About the author – The study of gender – Researching sex and gender – Gender stereotypes: masculinity and femininity – Hormones and chromosomes – Theories of gender development – Developing gender identity – Intelligence and cognitive abilities – Emotion – Relationships – Sexuality – School – Careers and work – Health and fitness – Stress, coping, and psychopathology – Treatment for mental disorders – How different? – References – Index.
Section: xix, 539 pages ; 26 cm
Keywords: approches et analyses; biologie; comportements sexuels; cours; différence des sexes; discipline; discours dominant; identité sexuelle; maternité; paternité; premier cycle; psy4910; psychologie; relations amoureuses; santé; santé mentale; sciences; sciences humaines; sexisme; sexualité; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences sexuelles; études de genres

Intersectional pedagogy : Complicating identity and social justice - Case, Kim A. (Routledge, 2017)
Intersectional Pedagogy explores best practices for effective teaching and learning about intersections of identity as informed by intersectional theory. Formatted in three easy-to-follow sections, this collection explores the pedagogy of intersectionality to address lived experiences that result from privileged and oppressed identities. After an initial overview of intersectional foundations and theory, the collection offers classroom strategies and approaches for teaching and learning about intersectionality and social justice. With contributions from scholars in education, psychology, sociology and women’s studies, Intersectional Pedagogy include a range of disciplinary perspectives and evidence-based pedagogy.
Keywords: approches et analyses; discipline; formations; féminisme décolonial; identités; intersectionnalité; justice sociale; outils; ouvrages de références; psychologie; pédagogie; ressource en ligne; sciences de l'éducation; sciences humaines; sociologie; thématiques; études de genres

The lived experiences of black undergraduate lesbian students at a rural South African university - Nela, K.; Vawdab, N.; Mbokodoc, L.; Govender, S. (Gender and Behaviour, 2017)
Malgré l'acceptation croissante des personnes lesbiennes, gays, bisexuelles, transgenres et intersexes (LGBTI), de nombreuses études indiquent encore que de nombreuses discriminations existent toujours. Les lesbiennes d'Afrique australe sont quotidiennement victimes de violences physiques et verbales et de viols correctifs. Le but de cette étude était d'explorer les expériences vécues par des étudiantes lesbiennes noires de premier cycle dans une université rurale en Afrique du Sud. Une approche de recherche qualitative utilisant un plan de recherche phénoménologique a été utilisée. L'échantillon était composé de quinze étudiantes lesbiennes noires de premier cycle âgées de 18 à 25 ans. Les données ont été collectées dans deux groupes de discussion et analysées à l'aide d'une analyse phénoménologique interprétative (IPA). L'homophobie, le harcèlement, y compris les agressions physiques, et la non-acceptation étaient des expériences quotidiennes chez les participantes lesbiennes. Cela incluait la discrimination de la part des pairs, du personnel universitaire et des organisations religieuses. Des expériences positives, comme la rencontre de nouveaux amis partageant la même orientation sexuelle et la découverte de l'université comme espace libre pour explorer leur sexualité, ont été trouvées.
Number: 3
Keywords: afrique; afrique du sud; approches et analyses; discipline; droits des femmes*; hétérosexisme; lesbophobie; personnes lesbiennes; psychologie; ressource en ligne; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; étudiantes de premier cycle

Le rose et le bleu : la fabrique du féminin et du masculin - Beauvalet-Boutouyrie, Scarlett; Berthiaud, Emmanuelle (Belin, 2016)
Une histoire de l'étude biologique, des statuts, des droits, de l'éducation, des apparences et des rôles attendus des hommes et des femmes, du XVIe au XXIe siècle, qui interroge la fabrication des concepts de masculin et de féminin.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; approches et analyses; cours; discipline; histoire; histoire et politique; postmodernisme; premier cycle; psy4910; psychologie; périodes historiques; sciences humaines; sexe/genre; stéréotypes de genre; thématiques; études de genres

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

Lesbian camp: An unearthing - Nielsen, Elly-Jean (Journal of Lesbian Studies, 2016)
Camp—a sensibility, a style, and a form of artistic selfexpression—is an elusive concept said to be in the eye of the beholder. To refute Susan Sontag’s (1966) claims that camp is apolitical and not especially homosexual, a number of recent scholarly works have been geared toward revealing camp’s fundamental gayness. With the odd footnote aside, lesbian camp has been collapsed into the category of gay male camp, if not eclipsed entirely. Despite the negligible efforts made to legitimize lesbian camp, there are numerous salient cultural examples one might draw on to illustrate, typify, and substantiate a lesbian camp sensibility. I lay the ground work for this scholarly exercise by outlining various definitions and critiques of camp, and by discussing its history and application to queer theory. Then, to unveil lesbian camp, three nonmutually exclusive categories are discussed: classic, erotic, and radical. By gathering various strands of inquiry, and various textual examples (e.g., photography, artistic performances, and literary tropes), this article attempts to reach a more inclusive and nuanced understanding of lesbian camp.
Keywords: approches et analyses; butch/femme; discipline; personnes lesbiennes; psychologie; queer; ressource en ligne; sciences humaines

Genre et psychanalyse : la différence des sexes en question - Rassial, Jean-Jacques; Chevalier, Fanny; Colloque Genre et psychanalyse (Érès, 2016)
« La remise en cause de l’évidence naturelle jusque-là accordée à la différence des sexes occupe la scène des débats publics et se retrouve théorisée par l’émergence du concept de « genre » dans sa distinction d’avec le sexe. La différenciation entre sexe et genre émerge d’une fracture avec l’idée que le sexe biologique déterminerait l’identité sexuée et sexuelle. Dans cette nouvelle terminologie, le sexe ne renvoie plus alors qu’à la dimension anatomique et biologique tandis que le genre réfère à la construction psychologique et sociale du sexe. Malgré la pluralité des théories auxquelles le genre a donné naissance, l’émergence de cette notion prend en compte que sexe anatomique, sexuation psychique et sexualité peuvent trouver des nouages autres que ceux promus par des normes confondues avec l’ordre naturel – nouage, souligne la psychanalyse, radicalement singulier pour chacun. Cet ouvrage propose une introduction à toute la complexité de ces questions. Il axe son propos sur les controverses entre les théories psychanalytiques et les études sur le genre, et ouvre le dialogue à la littérature, à la philosophie et au cinéma. Cette perspective pluridisciplinaire reflète ainsi l’hétérogénéité des différents abords et usages du genre. »– Résumé de l'éditeur.
Keywords: 2000 à aujourd'hui; LGBTQIA2+; cours; discipline; genre; identité sexuelle; identités LGBTQIA2+; post-structuralisme; premier cycle; psy4910; psychanalyse; psychologie; périodes historiques; ressource en ligne; sciences; sciences humaines; sexe/genre; thématiques

Pornography, feminist views of - Davis, Berta (The International Encyclopedia of Human Sexuality, 2015)
Feminist women's attitudes toward pornography are significantly polarized. Anti‐porn feminists have taken a position that pornography is degrading toward women, leads to distortion of healthy male‐female sexuality, leads to distorted images of the female body, increases male anxiety about sexual adequacy, sexual compulsivity, and increase violence toward women including rape and sexual harassment.
Disponible en ligne à l'adresse: https://doi-org.proxy.bibliotheques.uqam.ca/10.1002/9781118896877.wbiehs364
Keywords: approches et analyses; cours; discipline; féminisme anti-porn; féminisme pop; pornography; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; thématiques

Mon corps a-t-il un sexe? Sur le genre, dialogues entre biologies et sciences sociales - Gonthier, Josiane; Ruppli-Coursange, Mireille (La Découverte, 2015)
"Sexe" est l'un des mots de la langue française que les gens sans distinction de classe, de religion, d'apparence ou de profession, utilisent avec grand intérêt, qu'ils soient accoudés au zinc d'un bistrot ou à la paillasse d'un laboratoire de biologie moléculaire. Deux mises en scène distinctes, sociale ou scientifique ; deux scénarios différents : d'un côté, les histoires d'amour ou d'imaginaire sexuel, de l'autre, les recherches biologiques. Sous ce mot de "sexe", notre langue, si riche, produit une polysémie bien fâcheuse. L'ambition de ce volume, qui rassemble les contributions de chercheurs et chercheuses en sciences de la vie et en sciences humaines et sociales est de faire le point sur les connaissances concernant le sexe biologique et ses variations, dont on sait désormais qu'il ne permet pas de séparer les individus en deux catégories bien distinctes. Ce livre veut aussi évaluer l'impact du genre sur le développement du corps des êtres sexués et sur la construction de leur identité. Enfin, il cherche à apprécier dans quelle mesure les croyances liées au genre (bicatégorisation mâle-femelle stricte, supériorité masculine) ont pu influencer les recherches menées sur le sexe biologique. Et les témoignages de personnes intersexes et transgenres apportent sur la question de l'identité sexuée un éclairage complémentaire qui bouscule les "réponses" que donnent le plus souvent la médecine et le droit.
Section: 1 vol. (358 p. - [32] p. de pl.) : ill. en noir et en coul. ; 24 cm.
Keywords: approches et analyses; biologie; corps; cours; discipline; discours dominant; premier cycle; psy4910; psychologie; pédagogie; queer; sciences; sciences humaines; sciences sociales; sexualité; systèmes d'oppressions; thématiques; épistémologie; études de genres

Régulation des émotions et troubles de comportement chez des enfants d'âge préscolaire victimes d'agression sexuelle - Langevin, Rachel (Université du Québec à Montréal, 2015)
Être victime d'agression sexuelle (AS) durant l'enfance est associé à d'importants problèmes de santé mentale, physique et sexuelle à l'âge scolaire comme à l'âge adulte (Maniglia, 2009; Yancey, Hansen, & Naufel, 2011). Bien qu'une proportion non négligeable des AS de mineurs implique des enfants d'âge préscolaire, nous disposons de peu d'informations sur les corrélats des AS chez ces enfants. Les quelques études disponibles montrent, néanmoins, que leurs difficultés semblent similaires à celles des enfants d'âge scolaire (Berthelot, Langevin, & Hébert, 2012). On sait, par ailleurs, que les enfants victimes de diverses formes de maltraitance (négligence, agression physique et sexuelle) présentent davantage de difficultés de régulation des émotions que les enfants non maltraités. La régulation des émotions serait une variable médiatrice des liens entre maltraitance et troubles de comportement intériorisés et extériorisés (Alink, Cicchetti, Kim, & Rogosch, 2009). Cette thèse a pour objectif d'examiner les liens entre l'AS, la régulation des émotions et les troubles de comportement intériorisés et extériorisés chez des enfants d'âge préscolaire. Ses objectifs spécifiques, qui font chacun l'objet d'un article, sont les suivants : a) comparer les compétences de régulation des émotions d'enfants d'âge préscolaire victimes d'AS à celles d'enfants du même âge, mais n'ayant pas vécu un tel trauma, et b) examiner les liens entre AS, régulation des émotions et troubles de comportements intériorisés et extériorisés à l'aide d'une analyse de médiation. La thèse comprend quatre chapitres. Le premier chapitre offre une recension des écrits scientifiques portant sur les AS (définition, prévalence, corrélats), la régulation des émotions (définition et développement) et sur les liens empiriques et conceptuels entre régulation des émotions, santé mentale et maltraitance. Le premier article constitue le second chapitre. Les parents et les éducateurs ont évalué les compétences de régulation des émotions d'enfants d'âge préscolaire victimes d'AS (n = 62) et d'enfants du même âge n'ayant pas subi d'AS (n = 65) à l'aide du Emotion Regulation Checklist (ERC; Shields & Cicchetti, 1997). Les enfants ont, pour leur part, complété la MacArthur Story Stem Battery (Bretherton & Oppenheim, 2003) qui a ensuite été codifiée selon une grille, adaptée pour la présente étude, permettant d'obtenir des indices de leurs compétences de régulation des émotions (Langevin, Cassette, & Hébert, 2014). Les résultats indiquent que les enfants agressés sexuellement présentent de moins bonnes compétences de régulation des émotions que les enfants du groupe de comparaison sur plusieurs indicateurs provenant des trois évaluations. Les garçons victimes d'AS obtiennent des scores de régulation des émotions particulièrement faibles. Le deuxième article forme le troisième chapitre. Une analyse de médiation-modérée a servi à examiner les liens entre l'AS, la régulation des émotions, telle qu'évaluée par les parents et les éducateurs à l'aide du ERC, et les troubles de comportement intériorisés et extériorisés évalués par les parents à l'aide du Child Behavior Checklist (Achenbach & Rescorla, 2000; 2001). Les résultats montrent que l'association entre l'AS et les troubles intériorisés est entièrement médiatisée par la régulation des émotions, mais que la médiation est partielle pour ce qui est des troubles extériorisés. Le genre des enfants apparait comme une variable modératrice du lien entre l'AS et la régulation des émotions lorsque l'évaluation des parents est utilisée, alors qu'il modère l'association entre l'AS et les troubles de comportement lorsque l'évaluation des éducateurs est utilisée. Le quatrième et dernier chapitre de la thèse intègre les résultats obtenus dans les deux études et en souligne les contributions et limites. Enfin, ce chapitre aborde les pistes de recherche futures et les implications cliniques des résultats de la thèse. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : agression sexuelle, régulation des émotions, troubles de comportement intériorisés, troubles de comportement extériorisés, préscolaire
Keywords: IREF; amériques; discipline; enfants; mémoires/thèses; psychologie; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; violences; violences sexuelles

Dis/ability studies: theorising disablism and ableism - Goodley, Dan (Routledge, 2014)
In this ground-breaking new work, Dan Goodley makes the case for a novel, distinct, intellectual, and political project – dis/ability studies – an orientation that might encourage us to think again about the phenomena of disability and ability. Drawing on a range of interdisciplinary areas, including sociology, psychology, education, policy and cultural studies, this much needed text takes the most topical and important issues in critical disability theory, and pushes them into new theoretical territory. Goodley argues that we are entering a time of dis/ability studies, when both categories of disability and ability require expanding upon as a response to the global politics of neoliberal capitalism. Divided into two parts, the first section traces the dual processes of ableism and disablism, suggesting that one cannot exist without the other, and makes the case for a research-driven and intersectional analysis of dis/ability. The second section applies this new analytical framework to a range of critical topics, including: The biopolitics of dis/ability and debility Inclusive education Psychopathology Markets, communities and civil society. Dis/ability Studies provides much needed depth, texture and analysis in this emerging discipline. This accessible text will appeal to students and researchers of disability across a range of disciplines, as well as disability activists, policymakers, and practitioners working directly with disabled people.
Section: xvii, 204 pages ; 25 cm
Keywords: EDI; approches et analyses; capacitisme; care; corps; cours; discipline; interdisciplinarité; lit4700; premier cycle; psychologie; pédagogie; santé; sciences de l'éducation; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles

Resisting and conforming to the ‘lesbian look’: The importance of appearance norms for lesbian and bisexual women - Huxley, Caroline; Clarke, Victoria; Halliwell, Emma (Journal of Community & Applied Social Psychology, 2014)
Appearance is one way in which lesbian and bisexual identities and affiliation to lesbian, gay, bisexual (LGB) subculture can be demonstrated. ‘Butch’ and ‘androgynous’ styles have been used by lesbian women to communicate a non-heterosexual identity. However, some LGB appearance researchers have argued that there has been a mainstreaming and diversification of lesbian style in the last couple of decades, which has resulted in less distinction between lesbian and straight looks. This research draws on the Social Identity approach to explore contemporary style in lesbian and bisexual communities. Fifteen lesbian and bisexual women took part in semi-structured interviews which were analysed using thematic analysis. Although some participants reported a diversification of lesbian style, most used the term ‘butch’ to describe lesbian style, and a ‘boyish’ look was viewed as the most common contemporary lesbian style. By contrast, most participants could not identify distinct bisexual appearance norms. The data provide evidence of conflicting desires (and expectations) to visibly project social identity by conforming to specific lesbian styles, and to be an authentic, unique individual by resisting these subcultural styles
Keywords: 2000 à aujourd'hui; 2010-2019; discipline; europe; identités LGBTQIA2+; psychologie; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines

Contre l'indifférence des privilégiés : à quoi sert le care - Gilligan, Carole; Hochschild, Arlie; Tronto, Joan (Payot, 2013)
Comment résister à l'injustice ? Peut-on vaincre le " capitalisme émotionnel " ? Une éthique du care globale est-elle possible à l'heure des migrations transnationales ? Réunies pour la première fois, trois féministes et pionnières de la théorie et de l'éthique du care, la psychologue Carol Gilligan, la sociologue Arlie Hochschild et la politiste Joan Tronto, apportent leurs éléments de réponse avec, en ligne de mire, une injonction : encourager chacun à prendre ses responsabilités pour agir contre l'indifférence des privilégiés. Un événement intellectuel.
Keywords: approches et analyses; care; discipline; division sexuelle du travail; genre; patriarcat; privilèges; psychologie; science politique; science politique et droit; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; éthique

Un texte théorique libérateur - Molinier, Pascale; Fausto-Sterling, Anne (Les cinq sexes : pourquoi mâle et femelle ne sont pas suffisants, 2013)
Keywords: approches et analyses; cours; discipline; fem1000; premier cycle; psychologie; sciences humaines; sexe biologique; sexisme; systèmes d'oppressions

Étude-action sur les discriminations multifactorielles envers les femmes dans trois quartiers prioritaires lyonnais - Vinet, Elise; Cadel, Cynthia; Fieulaine, Nicolas; Colombani, Colline; Béal, Arnaud; Deschamps, Gaëlle; Levasseur, Elodie; Lin, Elise Chane Sha; Clement, Morgan; Laurent, Stéphanie; Vermillon, Marie-Amandine (GRePS-UL2, Région Rhône-Alpes, Ville de Lyon, 2013)
Les femmes des quartiers prioritaires lyonnais vivent-elles des formes spécifiques de discrimination, en particulier dans leurs usages de l’espace public (dans et hors-quartier) ainsi que dans leurs rapports aux offres socio-éducatives et de loisir au sein même de ces quartiers ? Ces discriminations tiennent-elles à leur sexe, à leur genre, à leur âge, à leur appartenance à un quartier classé en politique de la ville, à leur confession le cas échéant, à leur racisation par la société le cas échéant, racisation régulièrement qualifiée d’ « origine ethnique » ? A l’enchevêtrement inextricable de ces facteurs ? Le focus sur la catégorie « femme », bien que couplé à d’autres facteurs, ne risque-t-il pas d’invisibiliser d’autres formes de discriminations vécues sur ces territoires qui englobent la question des rapports sociaux de sexe sans s’y réduire pour autant ? Ces formes de discriminations sont-elles liées à des problématiques propres à ces territoires et/ou sont-elles liées à des problématiques systémiques venant s’incarner de diverses façons sur ces territoires ? Les professionnel-le-s territoriaux ainsi que celle-ceux des structures socio-éducatives et de loisir sont-elles en prise avec des formes de discrimination spécifiques ? Le cas échéant, se sentent-elles outillé-e-s pour y faire face ? Enfin, au vu de ces questionnements, quelles orientations sont envisageables pour l’action publique ? Au moment du bilan, c’est à l’ensemble de ces questions que s’attèle le présent rapport, rendant compte d’une étude-action commandée (par appel d’offre) par la Ville de Lyon (à l’intersection de deux délégations –Egalité femmes-hommes, temps de la ville et handicap et Politique de la ville- et accompagnée par la Mission Egalité de la Ville de Lyon) et conduite par l’équipe EgaliTer’ du laboratoire GRePS.
Keywords: approches et analyses; discipline; droits des femmes*; environnement; europe; france; projet charge mentale; psychologie; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques

Pascale Molinier, Le travail du care - Volery, Ingrid (La nouvelle revue du travail, 2013)
Paru aux Éditions La Dispute en 2013, le dernier ouvrage de Pascale Molinier s’attelle à ouvrir la boite noire du care, tel qu’il se déploie dans le quotidien d’un EHPAD de la région parisienne (renommé Villa Plénitude). S’inscrivant dans la lignée des travaux de psychologie et de philosophie qui en ont tenté une formalisation outre-Atlantique, son principal apport est de donner chair à une notion devenue « tarte-à-la-crème », en l’ancrant dans la réalité de situations professionnelles qui dé...
Keywords: care; discipline; europe; france; philosophie; projet charge mentale; psychologie; régions géographiques; sciences humaines; soins aux personnes âgées; thématiques; travail

Cerveau, hormones et sexe : des différences en question - Cossette, Louise (Les éditions du remue-ménage, 2012)
Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d’ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l’information diffusée tient davantage du préjugé, du parti pris idéologique, que d’une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd’hui encore ?C’est de ce constat, et d’un certain sentiment d’exaspération, qu’est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S’appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l’orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d’auteures féministes. Il ne s’agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ? Des textes de Line Chamberland, professeure au département de sexologie de l’UQAM et titulaire de la Chaire de recherche sur l’homophobie de l’UQAM ; Louise Cossette, professeure au département de psychologie de l’UQAM et membre de l’Institut de recherches et d’études féministes (IREF) de l’UQAM ; Chantal Maillé, professeure à l’Institut Simone de Beauvoir à l’Université Concordia et Catherine Vidal, neurobiologiste, directrice de recherche à l’Institut Pasteur de Paris.
Keywords: Brain; Human behavior; LGBTQIA2+; Men; Psychology; Sex differences; Sex differences (Psychology); Women; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; cycles supérieurs; discipline; discours dominant; fem1000; fem7000; genre; hétéronormativité; hétérosexisme; identités LGBTQIA2+; lit3220; premier cycle; psy4910; psychologie; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sexualité; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

The Sexualisation of Culture? - Gill, Rosalind (Social and Personality Psychology Compass, 2012)
This article examines contemporary debates about the ‘sexualisation of culture’. It sets out the context for claims that Western societies are becoming more sexualised and it explores a number of competing perspectives about sexualisation. It then looks in more detail at the nature of claims about sexualisation as they emerge from the different disciplinary perspectives of Psychology and Media and Cultural Studies, contrasting the strengths and weaknesses of each, and raising criticisms of both. In a final discussion section, the article considers the usefulness or otherwise of the notion of ‘sexualisation’ as analytic category and points to the need to go beyond polarised positions. It advocates a psychosocial approach that takes seriously differences and power in considering the contemporary proliferation of ‘sexualised’ images, practices and media
Keywords: approches et analyses; communication; corps; cours; discipline; discours dominant; discours médiatique; féminisme pop; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexualité; systèmes d'oppressions; thématiques; études culturelles

Young, Black and male : Exploring the intersections of racial and gender identity in an all-Black male high school - Rogers, Leoandra Onnie (New York University, 2012)
From popular culture to academia, there is national panic about the dismal life trajectories of Black males. This "Black male crisis" has contributed to emergent all-Black, all-male schools. Racial identity is commonly used to explain underperformance among Blacks, yet within-group gender disparity signifies the importance of gender relative to race. Minimal research exists on Black males' gender identities, and less on the intersections of gender and race. This longitudinal dissertation used quantitative and qualitative data to examine the development and intersections of racial and gender identity among Black adolescent males transitioning from co-educational grammar schools and entering the ninth grade at an all-Black, all-male high school. Findings are presented in two empirical papers. Paper 1 examined survey data collected from Black males (N = 183) to explain how boys' racial and gender identities were interrelated, changed over time, and influenced their psychological and academic adjustment. Results from the growth curve analysis revealed that boys' racial and gender identities were interrelated with each other and that higher levels of identity attachment were associated with better psychological and academic adjustment. Moreover, the strength of the relationship between gender identity and psychological adjustment increased over time, indicating that gender identity became increasingly important for boys' wellbeing. Paper 2 analyzed interview data with a subsample of Black males (n = 21) to examine how they resisted and accommodated racial and gender stereotypes. Results from the qualitative analysis revealed that boys were aware of the ways that racial and gender stereotypes overlap, but they responded to these stereotypes in different ways. Although some boys accommodated to both racial and gender stereotypes and others resisted these stereotypes, the majority of the boys responded by accommodating to gender stereotypes and resisting racial stereotypes. That is, they tended to perpetuate cultural stereotypes that require males to be the leader, emotionally stoic, and not to be feminine (i.e., gay) while challenging beliefs about the intellectual inferiority and incompetence of Black people. Findings are interpreted within the macro-context of cultural stereotypes and the micro-context of an all-Black male school. Implications for the study of identity, Black males, and single-sex education are discussed.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; adolescence; amériques; approches et analyses; chicago; discipline; genre; hommes* noirs; identité raciale; intersectionnalité; mémoires/thèses; philosophie; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes; étude longitudinale; étude qualitative; étude quantitative

Cerveau, sexe et préjugés - Vidal, Catherine (Cerveau, hormones et sexe: Des différences en question, 2012)
"Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d'ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l'information diffusée tient davantage du préjugé, du parti pris idéologique, que d'une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd'hui encore ? C'est de ce constat, et d'un certain sentiment d'exaspération, qu'est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S'appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l'orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d'auteures féministes. Il ne s'agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ?"–Page 4 de la couverture.
Keywords: amériques; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; discipline; discours dominant; fem1000; hétéronormativité; hétérosexisme; neurobiologie; neuropsychologie; pol4102; premier cycle; psy4910; psychologie; québec; régions géographiques; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

Brain storm: The flaws in the science of sex differences - Jordan-Young, Rebecca M. (Harvard University Press, 2010)
Jordan-Young has written a stunning book that demolishes most of the science associated with the dominant paradigm of the development of sex and gender identity, behavior, and orientation. The current paradigm, brain organization theory, proposes: "Because of early exposure to different sex hormones, males and females have different brains"; and these hormones also create "gay" and "straight" brains. Jordan-Young interviewed virtually every major researcher in the field and reviewed hundreds of published scientific papers. Her conclusion: "Brain organization theory is little more than an elaboration of longstanding folk tales about antagonistic male and female essences and how they connect to antagonistic male and female natures." She explains, in exquisite detail, the flaws in the underlying science, from experimental designs that make no statistical sense to "conceptually sloppy" definitions of male and female sexuality, contradictory results, and the social construction of normality. Her conclusion that the patterns we see are far more complicated than previously believed and due to a wider range of variables will shake up the research community and alter public perception.
Keywords: LGBTQIA2+; analyse critique; approches et analyses; corps; cours; différence des sexes; discipline; discours dominant; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; revue de la littérature; sciences; sciences humaines; sexe/genre; sexisme; sociologie; systèmes d'oppressions; thématiques

Intimate Justice: A Critical Analysis of Sexual Satisfaction - McClelland, Sara I. (Social and Personality Psychology Compass, 2010)
This article elaborates an intimate justice framework to help guide research on sexual satisfaction. Using a critical historiography approach, I examine the etiology and development of the psychological construct of “satisfaction” over the last century and argue that social and political antecedents to satisfaction ratings are an essential and under-theorized aspect of research in this field. By examining what are considered to be the most influential definitions in life satisfaction research, I identify conceptual gaps, oversights, and disagreements that characterize this body of work, and specifically its theoretical treatment of inequity. Moving to the intimate domain, I argue that the field of sexual satisfaction must include theories and methods that systematically consider the role of social and sexual stigmas as antecedents to sexual satisfaction ratings. In the conclusion, building from existing social justice theories, I propose an intimate justice framework as a means to guide research that can highlight issues of entitlement and deservingness in sexual satisfaction research. This is particularly important as sexual satisfaction is increasingly used as an indicator of individual and relational well-being; however, this construct is presently limited and inadequately measured for women and men who experience limited sexual rights in the socio-political domain because of their gender and/or sexual minority status.
Keywords: approches et analyses; capacitisme; cours; discipline; intersectionnalité; justice sociale; premier cycle; psychologie; racisme; ressource en ligne; sciences humaines; sex1920; sexisme; sexualité; systèmes d'oppressions; thématiques

Ethnic, Gender, and Acculturation Influences on Sexual Behaviors - Meston, Cindy M.; Ahrold, Tierney (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
Much research has been conducted on ethnic differences in sexuality, but few studies have systematically assessed the importance of acculturation in sexual behavior. The present study assessed general differences in normative sexual practices in healthy Euro-American, Asian, and Hispanic populations, using measures of acculturation to analyze the relative effects of heritage and mainstream cultures within each group. A total of 1,419 undergraduates (67% Euro-American, 17% Hispanic, 16% Asian; 33% men, 67% women) completed questionnaires which assessed sexual experience and causal sexual behaviors. In concordance with previous studies, Asians reported more conservative levels of sexual experience and frequency of sexual behaviors, fewer lifetime partners, and later ages of sexual debut than Euro-American or Hispanic counterparts. Hispanic reported sexual experiences similar to that of Euro-Americans. There was a significant interaction between mainstream and heritage acculturation in predicting number of lifetime sexual partners in Asian women such that the relationship between heritage acculturation and casual sexual behavior was stronger at lower levels of mainstream acculturation. On the other hand, in Hispanic men, higher levels of mainstream acculturation predicted more casual sexual behavior (one-time sexual encounters and number of lifetime sexual partners) when heritage acculturation was low but less casual sexual behavior when heritage acculturation was high. These results suggest that, for sexual behavior, Hispanic men follow an “ethnogenesis” model of acculturation while Asian women follow an “assimilation” model of acculturation.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexualité; thématiques; états-unis

Diversité sexuelle et constructions de genre - Chamberland, Line; Frank, Blye W.; Ristock, Janice L. (Presses de l'Universite du Quebec, 2009)
Les sciences sociales et épidémiologiques contemporaines tendent de plus en plus à prendre en compte la question du genre dans leurs théories sur les orientations sexuelles. Elle mettent ainsi en évidence les diverses articulations entre les formes de sexisme et d'homophobie, et leurs impacts différenciés selon les constructions du genre et les orientations sexuelles, de même qu'en fonction du contexte socioculturel dans lequel elles se situent. Réalisé avec l'appui de l'équipe pancanadienne Sexualités et genres, vulnérabilité et résilience (SVR), cet ouvrage regroupe des contributions de chercheurs francophones et anglophones du Québec, du Canada, de la France et de la Suisse romande, qui examinent les dimensions socioéconomiques, progessionnelles, familiales, relationnelles et psychologiques afin de saisir les variations liées au genre au sein des minorités sexuelles. Faisant appel à des résultats de travaux multidisciplinaires qui s'appuient sur des méthodologies de types quantitatif et qualitatif, ce livre met en lumière des processus contribuant aux inégalités sociales dans les champs de l'éducation, de l'économie et de la santé, et à des condition de vulnérabilité qui affectent l'estime de soi, les réseaux de soutien et la vie sociale. Les recherches observent des modes de résilience significatifs qui, là encore, peuvent varier en fonction du genre, suggérent ainsi sa prise en compte dans les interventions.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; lesbophobie; premier cycle; psy4910; psychologie; rapports sociaux de sexe; ressource en ligne; sciences humaines; sciences sociales; sexe/genre; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; théorie du genre; épistémologie; études de genres

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Intersections: cultures, sexualités et genres - Brotman, Shari L.; Lévy, Joseph J. (Presses de l'Université du Québec, 2008)
Les intersections entre la culture, le genre et la sexualité retiennent aujourd’hui l’attention des chercheurs qui travaillent sur la diversité sexuelle, une tendance que l’on rencontre dans l’espace québécois et canadien. Plusieurs études ont ainsi porté sur ces enjeux parmi les autochtones et les groupes ethnoculturels. Cet ouvrage collectif, réalisé par des chercheurs, anglophones et francophones, de l’équipe pancanadienne Sexualités, Vulnérabilités et Résilience, présente ainsi un ensemble de travaux qui font le point sur ces questions. Les dimensions théoriques et méthodologiques sont ainsi cernées et des études empiriques, faisant appel à des approches quantitatives et qualitatives, traitent des trajectoires et des identités parmi différentes populations, des problèmes de santé auxquels elles peuvent être confrontées et des variations dans les usages sociosexuels d’Internet. Ce tour d’horizon aide à mieux comprendre la complexité des intersections touchant les identités sexuelles et les dimensions culturelles et suggère des pistes de recherche et d’intervention à développer.
Section: xvi, 474 pages ; 23 cm
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; identités LGBTQIA2+; intersectionnalité; premier cycle; psychologie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexologie; sexualité; thématiques; travail social

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Une voix différente : pour une éthique du care - Gilligan, Carol (Flammarion, 2008)
La morale a-t-elle un sexe ? Les femmes et les hommes ont-ils un sens différent de la moralité ? Une telle question donne la mesure de l'immense débat qu'a suscité le livre de Carol Gilligan, catalyseur des réflexions féministes sur l'éthique du care (imparfaitement traduit par " sollicitude "). Si les analyses en termes de genre sont désormais connues, l'idée de care n'a pas rencontré un aussi large accueil. L'intérêt public grandissant pour les questions d'aide aux personnes vulnérables, et pour les problèmes sociaux et politiques engendrés par la situation inégalitaire des travailleuses/eurs du care et leur circulation au niveau mondial, a permis que les questions théoriques liées au care trouvent une nouvelle pertinence. Il a fallu également que se dissipe le rapport ombrageux du féminisme aux questions morales pour que le care ne soit pas rabattu sur l'idée d'un " service " contraint au profit des plus puissants. Aux Etats-Unis, Une voix différente est le texte le plus lu et le plus cité de la " seconde vague " du féminisme. Il a ouvert un débat politique crucial, entre éthique de la justice et éthique du care, entre une moralité centrée sur l'équité, l'impartialité et l'autonomie et une moralité formulée " d'une voix différente ", reconnue le plus souvent dans l'expérience des femmes, et fondée non sur des principes mais sur une question : comment faire, dans une situation donnée, pour préserver et entretenir les relations humaines qui y sont en jeu ?
Première publication 1982. Chapitre 2 donné en lecture dans le cours PHI4336.
Keywords: 1900-1999; amériques; care; cours; discipline; fem1000; har4600; phi4336; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis; éthique

The Politics of Protection: Body Image, Social Pressures, and the Misrepresentation of Young Black Women - Poran, Maya A. (Sex Roles : A Journal of Research, 2006)
As part of a larger multi-method study, 15 Black women college students participated in focus group discussions on the body. Contrary to popular theories that propose that Black women are protected by a “Black Culture” that buffers them from negative effects of body representations—thereby leaving them with higher body esteem—the themes that emerged in the focus group discussions indicate that young Black women are indeed feeling (1) pressures to be thin, (2) pressures from the preferences of men of diverse ethnicities, (3) competition with other Black women in the realms of beauty, and (4) a strong sense of being misrepresented by media images of thin Black women. These results not only indicate that body image issues are of real pressing concern to young Black women, but that psychological research methodologies may be adding to the misrepresentation of young Black women and their struggles. Qualitative methods must be utilized in order to hear more clearly the voices of Women of Color.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; image corporelle; intersectionnalité; new york; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; états-unis

Grossesse hors mariage dans les familles haïtiennes - Raphaël, Frantz (Santé mentale au Québec, 2006)
Des grossesses précoces chez des jeunes adolescentes haïtiennes de Montréal entraînent des situations de crise qui touchent plusieurs familles, en plus d’interpeller et d’impliquer des intervenants de diverses disciplines. Le sujet, abordé dans un contexte transculturel, fait référence au biculturalisme haïtien, tant en Haïti qu’en terre étrangère. Dans cet article, l’auteur aborde plus particulièrement la situation des Haïtiens dans le contexte québécois. L’analyse de l’attitude des parents des deux groupes culturels, occidentalisé et créole, constitue une lumière médiatrice dans les relations d’aide ou d’intervention psychothérapeutique. Dans la communauté haïtienne, les problèmes d’identité culturelle d’une part, et, le manque d’affiliation à la famille, d’autre part, sont à la base des conflits entre parents et enfants. L’auteur conclut avec des propositions dans le but d’améliorer l’efficacité des interventions avec ces familles dans leur processus d’adaptation migratoire.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; conflit familial; cours; discipline; grossesse hors mariage; haïti; justice sociale; maternité; montréal; premier cycle; psychologie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; thématiques

Abused women and survivor therapy - Walker, Lenore E. (American Psychological Association, 2006)
Dans ce manuel de traitement de pointe, Lenore E. A. Walker soutient que les psychothérapies traditionnelles pour les victimes de traumatismes ont été insuffisantes pour traiter les femmes maltraitées. Alors que le problème de la violence à l'égard des femmes continue de tourmenter la société, couvrant tous les secteurs démographiques, Walker décrit des modifications essentielles à la pratique traditionnelle qui permettront aux praticiens de travailler plus efficacement avec les femmes victimes de violence. Ces modifications aboutissent à une compilation intégrée des stratégies d'évaluation et d'intervention les plus réussies, appelées « thérapie de survivant ». La thérapie des femmes maltraitées et des survivants discute des principales formes de violence subies par les femmes : viol et agression sexuelle, coups de feu, abus sexuels commis par des thérapeutes et discrimination/harcèlement sexuel sur le lieu de travail. Walker examine les effets du sexe, de la race, de l'ethnicité, de la culture et de l'orientation sexuelle sur chaque forme d'abus ; discute des considérations cliniques et des approches de traitement ; évalue les instruments d'évaluation couramment utilisés ; et analyse les problèmes médico-légaux dans les cas impliquant la violence contre les femmes. Walker soutient que les modèles de traitement réussis doivent tenir compte de l'impact spécifique des diverses formes d'abus, de la réponse psychologique unique de l'individu au monde, de l'impact de la socialisation traditionnelle des femmes et des hommes, et du transfert de thérapeutes et du contre-transfert. Ces considérations peuvent être appliquées au cours d'une thérapie qui cherche à réautonomiser les femmes maltraitées en les aidant à retrouver leur estime de soi, à rétablir des relations saines et à retrouver un sentiment de contrôle et de choix dans leur vie. La thérapie des femmes maltraitées et des survivants aide les praticien.nes nouvellement formé.e.s ainsi que le praticien.ne expérimenté.e à identifier, évaluer et traiter les femmes qui ont été maltraitées physiquement, sexuellement ou psychologiquement.
Keywords: approches et analyses; cours; discipline; intersectionnalité; psychologie; santé; santé mentale; sciences humaines; thématiques; traumatismes; trs3500; violences; violences conjugales; violences sexuelles

Cerveau, sexe et pouvoir - Vidal, Catherine; Benoit-Browaeys, Dorothée. (Belin, 2005)
À la lumière des connaissances actuelles en neurosciences, on serait tenté de croire que les vieux préjugés sur les différences biologiques entre les hommes et les femmes ont été balayés. Ce n'est manifestement pas le cas : médias et ouvrages de vulgarisation prétendent que les femmes sont " naturellement " bavardes et incapables de lire une carte routière, tandis que les hommes sont nés bons en maths et compétitifs. Ces discours laissent croire que nos aptitudes, nos émotions, nos valeurs sont tablées dans des structures mentales immuables depuis les temps préhistoriques. Cet ouvrage, qui s'adresse à un large public, replace le débat autour de la différence des sexes sur un terrain scientifique rigoureux, au-delà des idées reçues. L'enjeu est de comprendre le rôle de la biologie, mais aussi l'influence de l'environnement social et culturel dans la construction de nos identités d'hommes et de femmes. Notre destin n'est pas inscrit dans notre cerveau! [Source : d'après la 4e de couv.].
Keywords: 2000 à aujourd'hui; approches et analyses; corps; cours; discipline; discours dominant; inégalités; neuropsychologie; neurosciences; premier cycle; psy4910; psychologie; périodes historiques; sciences; sciences humaines; sexe/genre; sexisme; systèmes d'oppressions; thématiques

Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques

The impact of culture and minority status on women's experience of domestic violence - Kasturirangan, Aarati; Krishnan, Sandhya; Riger, Stephanie (Trauma, violence & abuse, 2004)
The influence of culture and ethnic background on women’s experience of domestic violence has been explored in research only recently. Here the authors review research about the impact of culture and minority status in the United States on women’s experience of domestic violence, considering family structure,immigration, acculturation, oppression, and community response. The authors encourage researchers and service providers to acknowledge the effects on women of sociopolitical dynamics, including racism, and to identify specific aspects of culture that are relevant to intimate partner abuse.
Keywords: amériques; approches et analyses; cours; discipline; intersectionnalité; justice sociale; pauvreté; premier cycle; psychologie; racisme; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

A quest for authenticity: Contemporary butch gender - Levitt, Heidi M.; Hiestand, Katherine R. (Sex Roles : A Journal of Research, 2004)
Un modèle d'identité butch contemporaine a été construit à partir de l'analyse d'une série d'entretiens semi-structurés avec des femmes identifiées comme butch qui ont décrit leur genre en relation avec leurs propres expériences et croyances. Le processus analytique impliquait une approche théorique fondée (Glaser & Strauss, 1967). Les résultats de l'étude décrivent comment les femmes identifiées comme butch conceptualisent leur identité de genre et comment cela affecte leurs relations sociales au sein des communautés lesbiennes et hétérosexuelles. La catégorie centrale de ce modèle (c.-à-d. Une quête d'authenticité) définit l'identité butch comme impliquant un processus continu de négociation entre un sens essentiel du genre lesbien et des exigences de présentation du genre qui sont comprises en relation avec la signification et la signification des genres à travers les contextes sociaux. . (Enregistrement de la base de données PsycINFO (c) 2019 APA, tous droits réservés)
Keywords: 2000 à aujourd'hui; 2000-2009; butch/femme; discipline; identités LGBTQIA2+; psychologie; périodes historiques; ressource en ligne; sciences humaines

La haine et l'amour, la boîte noire du féminisme? Une critique de l'éthique du dévouement - Molinier, Pascale (Nouvelles Questions Feministes, 2004)
Les soins étant réalisés majoritairement par des femmes, on tend à considérer l’amour (des malades, des enfants) « naturel » et normal. Or, le travail de soin peut également générer de la haine envers les personnes dépendantes. Celle-ci n’est pas moins normale que l’amour et sa prise en compte modifie l’analyse des situations de soins. Pour l’heure, la haine est occultée dans les traditions savantes, en particulier dans les théories de l’éthique du dévouement, comme dans les témoignages des travailleuses, ainsi que le suggère une enquête réalisée auprès d’auxiliaires de puériculture. Il en résulte un déficit de visibilité du travail qui permet de conjurer la haine et la violence
Keywords: approches et analyses; care; discipline; discours dominant; projet charge mentale; psychologie; ressource en ligne; sciences humaines; sexisme; soins aux enfants; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; violences

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Butch/Femme in the personal advertisements of lesbians - Smith, Christine A.; Stillman, Shannon (Journal of Lesbian Studies, 2002)
Personal advertisements placed by lesbians were examined to determine how often butch/femme descriptors were used: (a) as a form of self-identification or (b) to indicate the type of partner being sought. The 388 personal advertisements were drawn from 16 alternative newspapers around the U.S., as well as from one Internet site (Qworld) that contained personal ads by lesbians. Each advertisement was coded for the presence or absence of butch/femme descriptors. The majority of advertisers did not mention butch or femme labels either in terms of self-identity or type of partner sought. Among the minority of advertisers who self-identified as butch or femme, more described themselves as femme than butch. Among advertisers seeking butch or femme partners, femme partners were sought most often. Explanations for the preference for femme lesbians were explored
Keywords: amériques; butch/femme; discipline; identités LGBTQIA2+; psychologie; ressource en ligne; régions géographiques; sciences humaines; états-unis

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

Heterosexuals' use of "fag" and "queer" to deride one another: a contributor to heterosexism and stigma - Burn, S M (Journal of homosexuality, 2000)
This paper is on heterosexuals' use of words such as "fag" and "queer" to refer to one another in an insulting manner. This behavior perpetuates heterosexism and the stigmatization of gays. Two hundred and fifty-seven university students (73% Euro-American) served as participants. Males exhibited more anti-gay prejudice and anti-gay behavior than females. Heterosexual males frequently used words such as "fag" and "queer" to put one another down. Anti-homosexual prejudice was predictive of anti-gay behavior. However, approximately half of those who engaged in the behavior were not strongly anti-homosexual. For these individuals, the behavior may win approval from their social group. Awareness campaigns and peer reminders that the derisive use of "fag" and "queer" harms homosexuals may be effective in changing this group. It is more difficult to reduce this behavior in individuals with strong anti-homosexual attitudes. The role of individuals and educational and work organizations in bringing about change is discussed.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; homophobie; hétérosexisme; insultes; premier cycle; psychologie; sciences humaines; soc2014; systèmes d'oppressions; thématiques

Life with the first baby: women's satisfaction with the division of roles - Cappuccini, G.; Cochrane, R. (Journal of Reproductive and Infant Psychology, 2000)
The ways parents divide their roles after their first child is born is a particularly complex arena. The success of negotiations within this close personal relationship may be central to the future of the new family. Women and their partners were surveyed in late pregnancy and 6 months after the birth. Their attitudes to role division remained largely non-traditional after the birth, even though most of them had incorporated some traditional elements into their behaviour. Emotional support received from their partners was important to women's satisfaction with role division, which had fallen only slightly after the birth. Eight of the women were interviewed in depth to explore why it might be that satisfaction with role division tended to remain high after the birth, despite the division usually not being what they had hoped for. Contributory factors may include changes in emphasis in the division of breadwinning and the maintenance of overall responsibility for traditional role areas despite sharing of tasks.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; europe; hétérosexualité; inégalités; maternité; premier cycle; privilèges; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques

Identity, emotion, and feminist collective action - Hercus, Cheryl (Gender and Society, 1999)
This article explores the relationship between identity, emotion, and feminist collective action. Based on interview research, the analysis confirms the central importance of anger in collective action and its particular significance for feminist identity and activism. As an emotion thought deviant for women, the anger inherent in feminist collective action frames created problems for participants in terms of relationships with partners, friends, and work colleagues. Participants performed emotion work to deal with negative responses to their feminist identity, but this depleted emotional energy and created stress. Participation in movement events provided much-needed emotional support and an outlet for deviant emotions.
Keywords: 1900-1999; 1990-1999; australie; colère; discipline; militance; océanie; organisations féministes; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques; émotions; étude qualitative

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Section: x, 193 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

Only the Literal: The Contradictions of Anti-pornography Feminism - Segal, Lynne (Sexualities, 1998)
Within feminism, battles over pornography have become the wars without end. Despite the controversy it generates, the discourses of anti-pornography feminism have continued to make inroads into legal frameworks, most recently in Canada. This piece surveys the growth and questionable appeal of such feminist campaigning, under the theoretical leadership of Catharine MacKinnon: its rewriting of feminist theory; its parasitic relation to the authoritative, phallocentric discourses of gender and sexuality; its alliance with the most reductive, behaviouristic psychology; its disavowel of fantasy and psychic life; its provocative mirroring of both the style and content of the `pornography' it deplores; its unwavering pursuit of legal remedies which enhance the power of state regulation of sexuality; its threat to subversive expressions of women's sexual agency and repudiation of any possibilities for sexual resignifications.
Keywords: cours; discipline; droits des femmes*; histoire et politique; militance; premier cycle; psychologie; ressource en ligne; sciences humaines; sex1911; sexologie; sexualité; thématiques

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Fantasies of femininity: Reframing the boundaries of sex - Ussher, Jane M. (Rutgers University Press, 1997)
In Fantasies of Femininity, Jane Ussher focuses on unraveling the contradictory visions of feminine sexuality: the fact that representations of the definition of woman seethe with sexuality yet for centuries women have been condemned for exploring their own sexual desires. In her quest for the sources of feminine representation, Ussher interviewed dozens of women - as well as some men - and combed popular media - from Seventeen to Cosmopolitan and Dallas to Donahue - to identify what shapes women's symbolic images of sex and femininity. Ussher argues that women have effectively resisted and subverted these archetypal fantasies of femininity, and in the process of so doing, reframed the very boundaries of sex. In this way, she exposes as myth much of what we think we know about "woman" and about "sex."
Keywords: approches et analyses; cours; discipline; fem1000; inégalités; premier cycle; psychologie; sciences humaines; sexualité; sexualité féminine; stéréotypes; systèmes d'oppressions; thématiques; études culturelles

Garçons et filles : stéréotypes et réussite scolaire - Bouchard, Pierrette; St-Amant, Jean-Claude (Éditions du Remue-ménage, 1996)
En vue de comprendre les mécanismes menant à la réussite scolaire au secondaire, la recherche se penche sur les modèles d'identification qu'offrent, aux garçons et aux filles, les stéréotypes sexuels. Elle vérifie, à l'aide d'une enquête auprès de 24 écoles secondaires québécoises, le degré d'adhésion aux stéréotypes et son influence sur les rapports entretenus avec l'école. Elle démontre qu'un meilleur rendement scolaire passe par un affranchissement des modèles de sexe. Questionnaire en annexe.
Section: 300 pages ; 23 cm
Keywords: approches et analyses; cours; discipline; premier cycle; psy4910; psychologie; recherche quantitative; sciences humaines; sexisme; stéréotypes de genre; systèmes d'oppressions; systèmes éducatifs; études de genres

The social construction of heterosexuality - Wilkinson, Sue; Kitzinger, Celia (Journal of Gender Studies, 1994)
Looks at some of the key issues raised by a tradition of social constructionist work on homosexuality, focusing on the nature of heterosexuality, heterosexual self-identification and the relationship between heterosexual sexual behavior and sexual identity. Political and theorectical importance of a sustained analysis of the functions and utility of heterosexuality; Impact of social constructionist theory on research relating to lesbians and gay men.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; cours; discipline; histoire et politique; premier cycle; psychologie; périodes historiques; sciences humaines; soc2014; sociologie; thématiques

The interpretation of the flesh: Freud and femininity - Brennan, Teresa (Routledge, 1992)
The 'riddle of femininity', like Freud's reference to women's sexuality as a 'dark continent', has been treated as a romantic aside or a sexist evasion rather than as a problem to be solved. In this first comprehensive study, Teresa Brennan suggests that by placing these ideas in the context of Freud's work as a whole, we will begin to understand why femininity was such a riddle for Freud. Brennan argues that by turning to Freud's work and his concrete questions about femininity, a psychical state which occurs in men and women alike, the problem is clearly a soluble one, provided that Freud's concern with energy is taken into account. The real riddle of femininity is as much a problem for thinking about physicality as a problem for the subject who suffers from what Freud described as 'femininity's negative effects on curiosity, intelligence and activity.
Keywords: 1900-1999; cours; discipline; fem1000; féminité; histoire; premier cycle; psychanalyse; psychologie; périodes historiques; ressource en ligne; sciences; sciences humaines; thématiques; violences

J'aime à toi : esquisse d'une félicité dans l'histoire - Irigaray, Luce (Grasset, 1992)
Qui es-tu, toi qui n'es, ne seras jamais moi ni mien ? Je t'écoute comme la révélation d'une vérité irréductible à moi. Tu m'as saluée, reconnue. Tu interroges tes limites. Je te donne du silence où le futur de toi - et peut-être de moi avec toi - peut émerger et se fonder. Je ne m'approche pas immédiatement de toi. Je ne te connaîtrai jamais de manière absolue. Je laisse de l'air, de l'espace, du mystère autour de nous. Éveillée à toi, recueillie, j'invente des paroles qui te touchent de leur souffle sans t'enlever à toi. Cet abord intransitif cherche aide auprès de l'univers, de la beauté, de la sagesse, de l'Histoire. En cette uvre déjà, j'aime à toi. Puisse ce " à " garder l'intention entre nous encore et toujours vive, berceau de l'être que notre transcendance l'un à l'autre enfante. " Après une critique de la maîtrise de notre culture par le genre masculin et la définition de médiations nécessaires à la constitution du sujet féminin, Luce Irigaray élabore ici une dialectique de l'intersubjectivité fondée sur la différence sexuelle. J'aime à toi marque donc un nouveau temps dans l'ouvre de la philosophe, le premier ayant été ouvert par Speculum, De l'autre femme.
Keywords: 1900-1999; 1980-1989; cours; différence des sexes; discipline; europe; fem1000; france; philosophie; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; sujet féminin; thématiques; écriture des femmes*

La nature humaine est deux - Irigaray, Luce (J'aime à toi : esquisse d'une félicité dans l'histoire, 1992)
Keywords: 1900-1999; 1980-1989; cours; différence des sexes; discipline; europe; fem1000; france; philosophie; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; sujet féminin; thématiques; écriture des femmes*

Une si grande différence - Gilligan, Carol (Flammarion, 1986)
Cela fait des siècles que nous écoutons les voix des hommes et les théories que leur dicte leur expérience. Plus récemment, nous avons commencé, non seulement à remarquer le silence des femmes, mais aussi, la difficulté d'entendre ce qu'elles disent quand elles prennent la parole. " A partir de trois enquêtes psychologiques, Carol Gilligan montre bien que la grande différence entre le masculin et le féminin est une différence de formation et de comportement moral conduisant à deux types psychologiques bien distincts, les femmes se caractérisant par une éthique de sollicitude qui influence leur rapport avec autrui et leur sens des responsabilités. Best-seller aux U.S.A., Une si grande différence est un ouvrage capital du post-féminisme.
Keywords: 1900-1999; amériques; care; cours; différence des sexes; discipline; fem1000; postféminisme; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis; éthique

La différence des sexes : questions de psychologie - Hurtig, Marie Claude; Pichevin, Marie-France (Tierce, 1986)
Keywords: 1900-1999; cours; différence des sexes; discipline; europe; fem1000; france; premier cycle; psy4910; psychologie; périodes historiques; régions géographiques; sciences humaines

Fonctionnalisme, darwinisme et psychologie des femmes. Études d'un mythe social - Schields, Stéphanie A. (La différence des sexes : questions de psychologie, 1986)
Keywords: 1900-1999; approches et analyses; cours; différence des sexes; discipline; europe; fem1000; france; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Les éditions du remue-ménage, 1983)
Les textes Morgan, R. (1983). La pornographie et le viol : théorie et pratique et Dworkin, A. (1983). Pour les hommes, liberté d’expression. Pour les femmes, silence, s’il vous plaît ont été donné en lecture au corus SEX1911.
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis

Ce sexe qui n'en est pas un - Irigaray, Luce (Les Éditions de Minuit, 1977)
Comment parler de l’autre côté, se demanda Alice. Car, en fait de merveilles, elle avait découvert qu’elle était plus d’une, et qu’une seule langue ne pouvait signifier ce qui avait lieu entre elles. Il fallait pourtant essayer de se faire entendre. Alors, s’appliquant, elle reprit : Que dire d’une sexualité féminine autre ? Autre que celle prescrite dans et par l’économie du pouvoir phallique. Autre que celle encore et toujours décrite – et normalisée – par la psychanalyse. Comment inventer, ou retrouver, son langage ? Comment interpréter le fonctionnement social à partir de l’exploitation des corps sexués des femmes ? Que peut être, dès lors, leur action par rapport au politique? Doivent-elles ou non intervenir dans les institutions ? Par quel biais échapper à la culture patriarcale ? Quelles questions poser à son discours ? À ses théories ? À ses sciences ? Comment les énoncer pour qu’elles ne soient pas, à nouveau, soumises à la censure ou au refoulement ? Mais aussi : comment déjà parler femme ? En retraversant le discours dominant. En interrogeant la maîtrise des hommes. En parlant aux femmes, entre femmes. Questions – parmi d’autres – qui s’interrogent et se répondent dans plusieurs langues, sur plusieurs tons, à plusieurs voix. Déconcertant l’uniformité d’un discours, la monotonie d’un genre, l’autocratie d’un sexe. Innombrables les désirs des femmes, et jamais réductibles à l’un ni à son multiple. Le jour était déjà levé depuis longtemps. Une histoire n’en finissait pas d’imposer son ordre. De l’obliger à s’exposer dans une clarté un peu froide. Dans l’attente d’un autre matin, elle repassa derrière le miroir, et elle se retrouva entre elles toute(s). Luce Irigaray
http://catalogue.bnf.fr/ark:/12148/cb345889016
Keywords: 1900-1999; 1970-1979; corps; cours; cycles supérieurs; différence des sexes; discipline; europe; fem1000; fem7000; france; har4600; langage féminin; lit3220; premier cycle; psy4910; psychanalyse; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualité féminine; thématiques; écriture des femmes*

Project Implicit
Test de préjugés inconscients
Keywords: approches et analyses; biais inconscients; cours; discipline; discours dominant; formations; inégalités; outils; pol5480; premier cycle; privilèges; psychologie; pédagogie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences